Protein Processing in Plant Mitochondria Compared to Yeast and Mammals - Heidorn-Czarna, Malgorzata; Maziak, Agata; Janska, Hanna (Frontiers in Plant Science, 2022)
Limited proteolysis, called protein processing, is an essential post-translational mechanism that controls protein localization, activity, and in consequence, function. This process is prevalent for mitochondrial proteins, mainly synthesized as precursor proteins with N-terminal sequences (presequences) that act as targeting signals and are removed upon import into the organelle. Mitochondria have a distinct and highly conserved proteolytic system that includes proteases with sole function in presequence processing and proteases, which show diverse mitochondrial functions with limited proteolysis as an additional one. In virtually all mitochondria, the primary processing of N-terminal signals is catalyzed by the well-characterized mitochondrial processing peptidase (MPP). Subsequently, a second proteolytic cleavage occurs, leading to more stabilized residues at the newly formed N-terminus. Lately, mitochondrial proteases, ICP55 and OCT1, involved in proteolytic cleavage after MPP and their substrates have been described in the plant, yeast, and mammalian mitochondria. Mitochondrial proteins can also be processed by removing a peptide from their N- or C-terminus as a maturation step during insertion into the membrane or as a regulatory mechanism in maintaining their function. This type of limited proteolysis is characteristic for processing proteases, such as IMP and rhomboid proteases, or the general mitochondrial quality control proteases ATP23, m-AAA, i-AAA, and OMA1. Identification of processing protease substrates and defining their consensus cleavage motifs is now possible with the help of large-scale quantitative mass spectrometry-based N-terminomics, such as combined fractional diagonal chromatography (COFRADIC), charge-based fractional diagonal chromatography (ChaFRADIC), or terminal amine isotopic labeling of substrates (TAILS). This review summarizes the current knowledge on the characterization of mitochondrial processing peptidases and selected N-terminomics techniques used to uncover protease substrates in the plant, yeast, and mammalian mitochondria.